2021
DOI: 10.31234/osf.io/32nhp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pairwise comparison using a Bayesian selection algorithm: Efficient holistic measurement

Abstract: The method of pairwise comparison has been used in a wide range of contexts. In educational measurement, many pairwise comparisons are required for reliable measurement when the comparisons to be performed are selected using the commonly-used semi-random selection algorithm (SSA). We proposed a Bayesian selection algorithm (BSA) to obtain smaller standard errors of parameter estimates and higher reliability compared with the SSA, and we evaluated the performance of these algorithms in a simulation study. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…In addition to the claim of higher validity of comparative judgment, Pollitt (2012) claimed that comparative judgment also results in higher reliability compared to using rubrics or criteria lists. However, later research has shown that this claim is likely to be too optimistic (e.g., Bramley, 2015;Bramley & Vitello, 2018;Crompvoets, Béguin, & Sijtsma, 2020;2021).…”
Section: On the Bias And Stability Of The Results Of Comparative Judgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the claim of higher validity of comparative judgment, Pollitt (2012) claimed that comparative judgment also results in higher reliability compared to using rubrics or criteria lists. However, later research has shown that this claim is likely to be too optimistic (e.g., Bramley, 2015;Bramley & Vitello, 2018;Crompvoets, Béguin, & Sijtsma, 2020;2021).…”
Section: On the Bias And Stability Of The Results Of Comparative Judgmentmentioning
confidence: 99%
“…To explain why Pollitt's (2012) claim is too optimistic, we first define two types of reliability in the context of comparative judgment: the benchmark reliability (Crompvoets et al, 2020(Crompvoets et al, , 2021 and the Scale Separation Reliability (SSR; e.g., Bramley, 2015;Crompvoets et al, 2020). Both forms of reliability are based on parameters of the Bradley-Terry-Luce (BTL; Bradley & Terry, 1952;Luce, 1959) model.…”
Section: On the Bias And Stability Of The Results Of Comparative Judgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the claim of higher validity of comparative judgment, Pollitt (2012) claimed that comparative judgment also results in higher reliability compared to using rubrics or criteria lists. However, later research has shown that this claim is likely to be too optimistic for the reported numbers of comparisons per item (e.g., Bramley, 2015;Bramley and Vitello, 2018;Crompvoets et al, 2020;Crompvoets et al, 2021), and that the extent to which high reliability that can be obtained using comparative judgment is limited (Verhavert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To explain why Pollitt's (2012) claim is too optimistic, we first define two types of reliability in the context of comparative judgment: the benchmark reliability (Crompvoets et al, 2020(Crompvoets et al, , 2021 and the Scale Separation Reliability (SSR; e.g., Bramley, 2015;Crompvoets et al, 2020). Both forms of reliability are based on parameters of the Bradley-Terry-Luce (BTL; Bradley and Terry, 1952;Luce, 1959) model.…”
Section: Introductionmentioning
confidence: 99%